Comprehensive Analysis of Sex Differences at Disease Manifestation in ANCA-Associated Glomerulonephritis - Tampe, Désirée; Korsten, Peter; Ströbel, Philipp; Hakroush, Samy; Tampe, Björn (Frontiers in Immunology, 2021)
Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is a small vessel vasculitis affecting multiple organ systems, including the kidney. Besides investigations focusing on renal outcomes, sex differences associated with distinct clinical and histopathological findings in ANCA glomerulonephritis (GN) have not been systematically investigated. Therefore, we here aimed to systematically analyze sex differences in patients with AAV and biopsy-proven ANCA GN. We provide a comprehensive analysis of 53 kidney biopsies with ANCA GN retrospectively included between 2015 and 2020 and identified specific sex differences in ANCA GN concerning laboratory parameters and systematic scoring of renal histopathology glomerular tubulointerstitial lesions, and extrarenal manifestations of AAV. We did not observe any correlation between sex and short-term clinical AAV course or disease severity by comparing general AAV parameters. AAV manifestations in females occurred at an older age with more extrarenal joint involvement. Regarding histopathological findings, we again observed no sex difference among ANCA GN classification, but a significant correlation between females and distinct histopathological findings with less tubulointerstitial inflammation and vasculitis of peritubular capillaries. Finally, we here identified less associations between clusters of clinical, laboratory parameters, and histopathological findings in females as compared to males. These findings are of great relevance and further improve our understanding of sex differences in the pathogenesis of ANCA GN. While future studies about specific sex differences and conclusions in these clusters are crucial, our observations further support that sex differences are relevant and affect distinct parameters and influence clinical, laboratory parameters, and histopathological findings in AAV, particularly ANCA GN.